Metabolomic Markers of Southern Dietary Patterns in the Jackson Heart Study. Issue 8 (11th March 2021) - Rebholz, Casey M.; Gao, Yan; Talegawkar, Sameera; Tucker, Katherine L.; Colantonio, Lisandro D.; Muntner, Paul; Ngo, Debby; Chen, Zsu Zsu; Cruz, Daniel; Katz, Daniel H.; Tahir, Usman A.; Clish, Clary; et al.
Abstract : Scope: New biomarkers are needed that are representative of dietary intake. Methods and Results: We assess metabolites associated with Southern dietary patterns in 1401 Jackson Heart Study participants. Three dietary patterns are empirically derived using principal component analysis: meat and fast food, fish and vegetables, and starchy foods. We randomly select two subsets of the study population: two‐third sample for discovery ( n = 934) and one‐third sample for replication ( n = 467). Among the 327 metabolites analyzed, 14 are significantly associated with the meat and fast food dietary pattern, four are significantly associated with the fish and vegetables dietary pattern, and none are associated with the starchy foods dietary pattern in the discovery sample. In the replication sample, nine remain associated with the meat and fast food dietary pattern [indole‐3‐propanoic acid, C24:0 lysophosphatidylcholine (LPC), N‐methyl proline, proline betaine, C34:2 phosphatidylethanolamine (PE) plasmalogen, C36:5 PE plasmalogen, C38:5 PE plasmalogen, cotinine, hydroxyproline] and three remain associated with the fish and vegetables dietary pattern [1, 7‐dimethyluric acid, C22:6 lysophosphatidylethanolamine, docosahexaenoic acid (DHA)]. Conclusion: Twelve metabolites are discovered and replicated in association with dietary patterns detected in a Southern U.S. African‐American population, which could be useful as biomarkers of Southern dietary patterns. Abstract : New biomarkers are needed for the objective assessment of dietary intake. Eleven metabolites were discovered and replicated in association with dietary patterns detected in a Southern U.S. African‐American population, which could be useful as biomarkers of Southern dietary patterns.